NATO's strategic adaptation: Germany is the backbone for the alliance's military reorganisation - Claudia Major (Stiftung Wissenschaft und Politik (SWP), 2015)
In reaction to the Ukraine crisis, NATO allies decided at the September 2014 Summit in Wales on the most fundamental military adaptation of the Alliance since the end of the Cold War. The objective is a large scale reinforcement and reorganisation of defence capabilities. Collective defence has thereby been reinstated as the core task of NATO, requiring considerable political, military and financial input from all Allies. The focus of attention is, however, on Germany. First, Germany played a considerable part in shaping the Wales decisions. Second, the partners expect Germany to bear a substantial military and financial burden because of its economic strength. Third, Berlin placed itself under pressure to promote defence cooperation when it launched the framework nation concept in 2013. (SWP Comments)
Keywords: 320